Effects of Dried Distillers Grains in Supplements for Beef Cows During Late Gestation on Cow–Calf Performance and Metabolic Status - Johnnatan Castro Cabral Gonçalves; Jean Marcelo Albuquerque; Edinael Rodrigues de Almeida; Luanna Carla Coelho; José Augusto Moura Godinho; Lilian Yukie Pacheco Toma; Matheus Fellipe de Lana Ferreira; Luciana Navajas Rennó; Cláudia Batista Sampaio; Edenio Detmann; Sidnei Antônio Lopes (Animals, 2025)
Forty multiparous Nellore cows, with an average body weight, body condition score, and gestation days of 533 ± 32 kg, 5.7 ± 0.4 points, and 198 days, respectively, were managed under continuous grazing on a Urochloa decumbens pasture and either received or did not receive 1 kg/day of supplement varying in the levels of inclusion of dried distillers grains (DDG) (Control, 0% DDG, 42% DDG, or 84% DDG) during the last trimester of gestation. The objective was to evaluate the effects of prepartum DDG supplementation on performance, reproduction, fetal development, and calf performance. A quadratic effect of supplementation on BW variation pre- and postpartum was observed (p < 0.05), with cows treated with 42% DDG showing higher BW gain prepartum and low BW loss postpartum. Cows supplemented with 42% DDG had lower levels of non-esterified fatty acids and β-hydroxybutyrate prepartum (p < 0.05). However, body weight-related metrics, such as condition score, carcass traits, and metabolic indicators, varied only by measurement day (p < 0.05). No effect of supplementation was observed on fetal development, calf metabolic profile, milk yield, or postnatal calf performance (p > 0.05). It is recommended to include up to 42% DDG in supplements for beef cows during late gestation grazing on low-quality tropical forage conditions.